Prevalence of Anemia in Pregnant Women - Mutayyaba Majeed, Sidra Farooq, Tayyaba Rasheed, Zehra Niazi, Tuba Rasheed (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the prevalence of anemia in pregnant women in Punjab. Study Design: Cross-sectional study. Place and Duration of Study: Department of Obstetrics & Gynaecology, DHQ Hospital, Faisalabad from 1st October 2021 to 31st March 2022. Methodology: One hundred and fifty pregnant females were enrolled, clinically assessed for their anemic status and were divided into two groups in reference to suspicion of anemia. Group A had those pregnant females who were suspected for anemia while group B were with no suspicion of anemia. Both Group A and Group B had 75 pregnant females. The complete blood count and serum analysis of ferritin, iron and folic acid was performed in each patient after withdrawal of 5cc blood. The demographic details of each patient as well as dietary habits in context of meat, fruit and vegetables from last month were also documented. Results: There were 37.3% pregnant females within suspected anemia group while 36% pregnant females in no suspected anemia group. The frequency of abortion was higher in group A than B with an odds ration as 1.17-1.18. There were more over weight and obese women in suspected anemia Group A while under-weight were more common in Group B. Pregnant females in Group A were consuming less amount of meat, fruit and vegetables than females in group B. The suspected anemia pregnant females blood analysis reports showed 74.6% been iron deficient in comparison with 41.3% non-suspected pregnant females Conclusion: Anemia was prevalent in both suspected and unsuspected group and 75% of the suspected anemia group were also iron deficient. Keywords: Iron deficiency anemia, Pregnancy, Hemoglobin, Incidence, Developing countries